DISTRIBUTION FEATURES AND BIOLOGICAL CHARACTERISTICS OF ENDEMIC PLANT OF WESTERN TIEN-SHAN ERANTHIS LONGISTIPITATA (Experimental biology, 2023)
The article provides updated data on the distribution of the endemic species E.longistipitata on the territory of the Aksu-Jabagly Reserve. The first population is the Taldy-Bulak Gorge (left bank of the stream); the second population is the Zhetimsai Gorge (left bank of the stream); the third population is the Valley of the Irsu River. Monitoring sites were created for all coenopopulations, the species density was calculated using the method of A.A.Uranov, the species composition was determined. The average density of E. longistipitata species varied from 14 to 22 pcs/2m2. The morphometric characteristics of the detected species growing in 3 different sites have been studied. The population of E.longistipitata growing in the valley of the Irsu River was marked by the maximum indicators (stem height, number of leaves and sepals). The plant community of 3 monitoring sites and the predominant soil type were determined.
Keywords: Eranthis longistipitata Regel, Western Tien Shan, Aksu Jabagly Nature Reserve, endemic, population density, morphometric characteristics